Synthesis of new zwitterionic surfactants and investigation of their surface active and thermodynamic properties - Ahmed S. Mansour; M. M. Abo-Aly; S. A. Rizk; Abdellatif M. M. Abd El Rahman; N. F. Ghaly; A. A. Ragab; A. M. Alsabagh (Scientific Reports)
Abstract This study focused on the synthesis of six bio-based zwitterionic surfactants derived from oleic acid to assess their applicability in different petroleum fields. The final bi-zwitterionic surfactants were synthesized from oleic acid, utilizing the double bond and carboxylic group. Friedel–Crafts alkylation, sulfonation, chlorination, amidation, and quaternization were performed to synthesize six bi-zwitterionic surfactants. The bi-quaternary surfactants derived from benzene are represented by the general formula Bi Q 10, BOAS (Amide), with the symbols BE, BP, and BPh. In contrast, those derived from naphthalene are represented by Bi Q 10, NOAS (Amide), with the symbols NE, NP, and NPh. The structures of these surfactants were confirmed using FT-IR and H1-NMR techniques. The surface activity and thermodynamic properties of the synthesized surfactants were analyzed through surface tension measurements conducted at various temperatures (30, 40, 50, and 60°C). Additionally, CMC, γ CMC , π CMC , Γ max , A min, and Pc 20 were measured. The thermodynamic variables for micellization and adsorption were also measured. The structural effect of the obtained surfactants was assessed. The maximum value of the structural effect was 4.33 KJmol-1, corresponding to BE. The results indicated that the negative values of ΔGads were greater than the negative values of ΔGmic, indicating that these surfactants are absorbed in the interface prior to the formation of micelles. The more negative values of ΔGads suggest that these surfactants are strongly adsorbed onto solid particles, such as sands and rocks, indicating their potential utilization in oil production in different petroleum fields.